Food insecurity in Sub-Saharan Africa: new estimates from household expenditure surveys - Smith, Lisa C.; Alderman, Harold; Aduayom, Dede (International Food Policy Research Institute, 2006)
This report introduces new estimates of food insecurity based on food acquisition data collected directly from households as part of national household expenditure surveys (HESs) conducted in 12 Sub-Saharan African countries.The report has three objectives: (1) to explore the extent and location of food insecurity across and within the countries; (2) to investigate the scientific merit of using the food data collected in HESs to measure food insecurity; and (3) to compare food insecurity estimates generated using HES data with those reported by FAO and explore the reasons for differences between the two.The overall purpose is to investigate how the data collected in HESs can be used to improve the accuracy accuracy of FAO’s estimates, which are being used to monitor the MDG hunger goal.The study is based on both diet quantity and diet quality indicators of food insecurity. The two main indicators of focus are the share of people consuming insufficient dietary energy, or the prevalence of “food energy deficiency,” and the share of households with low diet diversity.The study finds these to be valid indicators of food insecurity and to be reasonably reliably measured.They are also comparable across the study countries despite differing methods of data collection.